Clarity of Central Bank Communication About Inflation - Bulir, Ales (IMF Working Papers; Working Paper, 2012)
This paper examines whether the clarity of central bank communication about inflation has changed with the economic environment. We use readability statistics and content analysis to study the clarity of communication on the inflation outlook by seven central banks between 1997 and 2010. Overall, we find no strong indications that central banks were less clear in explaining their policies when faced with higher uncertainty or a less favorable inflation outlook. The global financial crisis, however, did have a negative impact on clarity of central bank communication.